2017
DOI: 10.3847/1538-4357/aa9e4f
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Hyperaccretion Inflow–Outflow Model. I. Long and Ultra-long Gamma-Ray Bursts

Abstract: Long-duration gamma-ray bursts (LGRBs) and ultra-LGRBs (ULGRBs) originate from collapsars, in the center of which a newborn rotating stellar-mass black hole (BH) surrounded by a massive accretion disk may form. In the scenario of BH hyperaccretion inflow-outflow model and BlandfordZnajek (BZ) mechanism to trigger gamma-ray bursts (GRBs), the real accretion rate to power a BZ jet is far lower than the mass supply rate from the progenitor star. The characteristics of the progenitor stars can be constrained by GR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 79 publications
(110 reference statements)
0
69
0
1
Order By: Relevance
“…Panchromatic studies of future FBOTs will clarify if AT 2018cow is a representative member of its class and will reveal the connection (or lack thereof) of FBOTs to other classes of explosive transients, like GRBs or TDEs (the only two types of transients that are known to show persistent and rapid X-ray variability so far). In this respect it is interesting to mention that hints for hard X-ray excesses have been reported in long GRBs Margutti et al 2008), which are central-engine powered explosions, and in ultra-long GRBs Bellm et al 2014), for which the connection to blue supergiant progenitors has already been suggested (e.g., Quataert & Kasen 2012;Gendre et al 2013;Nakauchi et al 2013;Wu et al 2013;Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Panchromatic studies of future FBOTs will clarify if AT 2018cow is a representative member of its class and will reveal the connection (or lack thereof) of FBOTs to other classes of explosive transients, like GRBs or TDEs (the only two types of transients that are known to show persistent and rapid X-ray variability so far). In this respect it is interesting to mention that hints for hard X-ray excesses have been reported in long GRBs Margutti et al 2008), which are central-engine powered explosions, and in ultra-long GRBs Bellm et al 2014), for which the connection to blue supergiant progenitors has already been suggested (e.g., Quataert & Kasen 2012;Gendre et al 2013;Nakauchi et al 2013;Wu et al 2013;Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This model therefore represents one of the best solutions for GRB 111209A/SN 2011kl presented so far. Liu et al (2018b) used prompt emission data to constrain the possible progenitor stars of GRBs of different duration within the framework of a BH hyper-accretion model. They found that ULGRBs such as GRB 111209A can only have progenitors of high mass and low metallicity, up to metal-free Pop III stars.…”
Section: Models For Gamma-ray Transients Of Extreme Durationmentioning
confidence: 99%
“…超长暴的前身星模型主要分为以下三种类型: 超 大质量恒星, 类似于Pop III Stars(蓝超巨星) [20,45,48,49] ; 白矮星的潮汐瓦解 [50,51] ; 特殊的中心引擎, 如新诞生的 磁星 [40] 、夸克星 [26] , 黑洞的超吸积 [52] 以及黑洞自旋衰 减提供能量 [53] 等. 我们将在下面的叙述中举例说明.…”
Section: 超长暴的前身星模型unclassified